Patient’s Perception of Hospital Pharmacists Roles: A Cross-Sectional Study in Two Nigerian Teaching Hospitals - Anene-Okeke, Chigozie Gloria; Nwachuya, Chukwuemeka Augustine; Ubaka, Chukwuemeka Michael; Ukwe, Chinwe Victoria (Indian Journal of Pharmacy Practice)
Background: Patients’ perception of healthcare services, including pharmacy, is crucial for evaluating service quality and satisfaction. This study explores patients’ perceptions of hospital pharmacists’ roles in Nigerian teaching hospitals and examines how socio-demographic factors influence these perceptions. Materials and Methods: A questionnaire-based survey was conducted among outpatients attending the University of Nigeria Teaching Hospital (UNTH) in Enugu State and Ahmadu Bello University Teaching Hospital (ABUTH) in Kaduna State. Data analysis included descriptive statistics (frequency, percentage, mean, and standard deviation) and Chi-square tests to examine associations between socio-demographic characteristics and perception scores. SPSS version 25 was used to analyze the data. The statistical significance level was set at p ≤ 0.05. Results: A total of 692 respondents participated in the study. Male respondents were 356 (51.4%), 428(61.8%) of the total respondents being married and 551 (79.6%) residing in urban areas. Patients expressed positive perceptions of hospital pharmacists’ essential roles with a score of 82.98±6.49 suggesting very favorable perception, including their expertise in drug-related inquiries and contributions to treatment. Marital status X2 (4) = 9.603, p = 0.048], educational level [X2 (4) = 15.381, p = 0.004], and income [X2 (4) = 14.907, p = 0.001] influenced perception scores. Conclusion: Patients in Nigerian teaching hospitals hold positive perceptions of hospital pharmacists’ roles, recognizing their importance in healthcare delivery. Socio-demographic influences on perception can guide strategies to enhance patient-pharmacist interactions and optimize pharmaceutical care delivery.
Keywords: Patients; Perception; Hospital; Pharmacists; Nigeria